YU YING-SHI’S UNDERSTANDING OF BUDDHISM AND HIS DISCUSSION OF THE NEW ZEN BUDDHISM - Wen-Shu Huang (PEOPLE: International Journal of Social Sciences, 2025)
Yu Ying-shi is a distinguished contemporary historian who has had significant engagement with Buddhism and Zen from his youth into his later years, with numerous writings addressing Buddhism and Zen topics. He fundamentally affirms that Buddhist doctrine is an important spiritual resource in the modern world. He believes that while Buddhism primarily advocates for renunciation of the world, the new Zen Buddhism shifts towards "worldly asceticism," having a profound impact.Yu’s understanding of Buddhism can be summarized in four key points: First, Buddhism is a highly developed and complex philosophical system. Second, Buddhism has integrated into Chinese culture through the reception of Daoist thought and has spread widely. Third, the high monks of Buddhism embody a "scholar’s" aspiration to "rescue all beings",which is deserving of respect. Fourth, Buddhism has an intangible influence, particularly the Mahayana spirit, which aids in the realization of the "inner sage" and "outer king".Regarding his evaluation of the new Zen Buddhism, it can be encapsulated in five points: First, Huineng established a new Zen Buddhism of revolutionary significance. Second, the core spirit of the new Zen Buddhism is "worldly asceticism".Third, the new Zen Buddhism advocates for a "not adhering and not separating" approach to transcendent world and real life. Fourth, the new Zen Buddhism stimulated the rise of Neo-Confucianism during the Song and Ming dynasties. Fifth, the new Zen Buddhism emphasizes "directly pointing to the mind", highlighting the role of the heart.In his view, the new Zen Buddhism’s shift towards the world combines the concepts of this shore and the other shore, resembling Western Protestant ethics. In comparison, the new Zen Buddhism proposed the idea of "worldly asceticism" earlier than Protestant Christianity, but in terms of historical and social impact, Protestantism undoubtedly has had a greater influence.